Transition metal sulfides for energy storage and conversion - Dangol, Raksha (Nanyang Technological University, 2020)
The investigation of the use of nanomaterials for the development of sustainable energy sources and energy storage devices are crucial in the current situation. Here, battery research and fuel cell are two of the most important areas of studies for driving future energy demand. Lithium batteries are presently used in most electronic devices for the storage of energy. However, to keep up with the demand of high energy and power density storage batteries, investigation of alternative battery materials is necessary. So, NiPS3, a representative member of ternary layered materials (MPS3) is studied as lithium-ion anode. It possesses a high theoretical capacity (1298 mAh g-1) of lithium-ion storage owing to the layered structure and good conductivity. So, the investigation of the properties of bulk and exfoliated NiPS3 are carried out. The exfoliated NiPS3 delivers the discharge capacity comparable to its theoretical capacity and a stable rate capability. This shows a good performance as anode material. The fuel cell is considered as a clean and sustainable form of energy storage, with hydrogen and oxygen as fuels. As the production of hydrogen and oxygen from water is an important electrochemical process, the process can be promoted by using a catalyst so that the energy consumed for their production is much lowered. Novel metal-based materials are the ideal electrocatalysts. So, the materials for replacing expensive catalysts are needed for commercial usage and development of this technology. The overpotential and Tafel slope of exfoliated NiPS3 to drive the OER is much lower than the commercial IrO2. The abundant edge sites are electrochemically active sites for oxygen evolution. Upon investigation, it was found that the activity was due to the formation of NiOOH catalyst which in turn increases hydrogen adsorption at active sites. As the utilization of LIB continues, the resources of lithium are becoming scarce and expensive. An alternative to lithium-ion battery is sodium-ion battery as sodium is abundant in nature and properties are similar to that of lithium. MoS2 is an interesting material because of facile synthesis routes and resemblance to graphene structure. Abstract ii However, its properties for battery and water splitting are still inadequate for commercial use. The theoretical calculations have shown that doping MoS2 is one of the methods to improve the electrochemical activity. So, MoS2 doped by Co delivers a high reversible specific capacity when used as SIB anode due to incorporation of conductive core and amorphous shell whereby conductivity is improved. As for HER activity, the hydrogen adsorption energy of MoS2 at S-edges is positive (nearly zero) and cobalt is negative in Volcano plot, when they are combined the synergistic effect will produce near zero hydrogen adsorption energy. Hence, the electrochemical HER are investigated by doping cobalt in amorphous MoS2. Thus, crystalline core-amorphous shell (Co4S3@MoS2) nanospheres have been synthesized by optimizing Co/Mo precursor ratios. The study shows that Co doping reduces the overpotential and Tafel slope drastically, leading to an improved HER performance. The major disadvantage of MoS2 in HER reaction is that it has slow kinetics which is shown in its high Tafel slope and resistance. So, a rational design to improve electron transfer and hydrogen adsorption/desorption is necessary. Therefore, MoS2 is grown on carbon cloth substrate along with cation and anion doping. Eventually, doping it with both Selenium and Vanadium simultaneously has demonstrated an excellent overpotential and Tafel slope with a long-term stable performance. Such performance is attributed to the high activity of active sites and low resistance of V and Se co-doped MoS2 grown on carbon cloth. Hence, the rational nanostructuring and design of nanomaterials based on transition metal sulfides are necessary for obtaining high electrochemical performance in their respective energy storage applications and devices.